MicroRNAs are differentially deregulated in mammary malignant phyllodes tumour. Issue 3 (2nd March 2015) - Tsang, Julia Y S; Ni, Yun‐Bi; Ng, Enders KO; Shin, Vivian Y; Mak, Ko‐Fung; Go, Edna May L; Tawasil, John; Chan, Siu‐Ki; Ko, Chun‐Wai; Kwong, Ava; Tse, Gary M
<x xml:space="preserve">Abstract</x> Aims MicroRNAs (miRs) have been shown to play important roles in tumour progression. Their expression pattern can be useful for cancer classification. However, little is known about miRs in mammary phyllodes tumours (PT). Methods and results In this study, polymerase chain reaction (PCR)‐based miR profiling was performed in a small PT cohort to identify deregulated miRs in malignant PT. The purported roles and targets of these miRs were further validated. Unsupervised clustering of miR expression profiling segregated PT into different grades, implicating the miR profile in PT classification. Among the deregulated miRs, miR‐21, miR‐335 and miR‐155 were validated to be higher in malignant than in lower‐grade PT in the independent cohort by quantitative PCR (qPCR) (P ≤ 0.032). Their expression correlated with some of the malignant histological features, including high stromal cellularity, nuclear pleomorphism and mitosis. Subsequent analysis of their downstream proteins, namely PTEN for miR‐21/miR‐155 and Rb for miR‐335, also showed an independent significant negative association between miR and protein expression. Conclusions Differential expression of miRs in PT could be useful in diagnosis and grading of PT. Their deregulated expression, together with the altered downstream targets, implicated their active involvement in PT malignant transformation.